Fatigue strength and weight optimization of threaded connections in tie-rods for aircraft structures. (2018) - Winklberger, Markus; Heftberger, Peter; Sattlecker, Mario; Schagerl, Martin
Abstract: Tie-rods are connecting elements used in an aircraft and they basically consist of a straight tube and two screwed in adapter ends. In order to optimize the tie-rod in terms of weight reduction a detailed knowledge of its fatigue strength is important. However, the complex load and contact distribution within the threaded connection between tube and adapter end make a secure and efficient fatigue design challenging. Moreover, the connection is realized with a thread insert to assure smooth adjustability of the adapter ends, which further increases the complexity of a fatigue strength assessment. Thus, cyclic fatigue tests with a load ratio of R = 0.01 are performed to investigate the influences of thread insert length and position on the fatigue life of three different configurations. The experimental results are explained by Finite Element analyses using a detailed Finite Element model of the threaded connection. Finally microscopic examinations as well as the Finite Element analyses are utilized to further optimize the threaded connection in terms of reduced weight and high fatigue strength.